Interim report: A randomized controlled trial comparing postoperative pain in single‐incision laparoscopic cholecystectomy and conventional laparoscopic cholecystectomy. Issue 1 (14th September 2012) - Chang, Stephen Kin Yong; Wang, Yi Liang; Shen, Liang; Iyer, Shridhar Ganpathi; Shaik, Ahmad Bin Syed Buhari; Lomanto, Davide
Abstract Introduction Single‐incision laparoscopic cholecystectomy (SILC) is increasingly practiced, but there have been no well‐powered randomized trials investigating the technique. This non‐inferiority trial aims to compare SILC with conventional four‐port laparoscopic cholecystectomy (LC) with postoperative pain as the primary endpoint. Methods We aim to randomize 100 patients into equal arms of SILC or LC. Exclusion criteria were: (i) acute cholecystitis; (ii) an ASA score of 3 or above; (iii) bleeding disorders; or (iv) previous upper abdominal surgery. Patients and postoperative assessors were blinded to the procedure received. The site and severity of pain was compared based on the visual analogue scale at 4 hours, 24 hours and 14 days postoperatively; non‐inferiority was assumed when the lower boundary of the 95% confidence interval of the difference was above −1, and superiority when P ≤ 0.05. Results We recruited 24 SILC and 26 LC patients. There were no conversions to open cholecystectomy or from SILC to LC. SILC was non‐inferior for pain at umbilical sites at rest and at extra‐umbilical sites at all times. At 24 hours postoperatively, SILC was associated with significantly less pain at extra‐umbilical sites (rest: P = 0.002; movement: P = 0.004). There were no incidents of biliary injury or retained gallstones. Of the 24 SILC patients, 12.5% had postoperative complications (vomiting, mild fluid overload, wound infection) compared with 0% of LC patients (P = 0.110); all complications resolved with conservative management. Operating time, analgesic use, return to function, and overall satisfaction did not differ significantly between the two groups. Conclusion SILC is associated with reduced pain and is feasible in routine surgical practice.